Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles